MOTIVASI BERTAHAN INDUSTRI KECIL: STUDI KASUS PADA PRODUSEN RITUAL IMLEK - Yoel Wibawatama Morita (Ma Chung Press, 2018)
Imlek is the culture of the Chinese which is celebrated new year Chinese in Indonesia. Chinese New Year celebrations associated with the festival commemorating the coming New Year, and related to Hungbao and Nian Gao. This study finds a unique phenomenon investigated from Indonesian manufacturers which produce Imlek ritual stuffs. The purpose of this study was to determine the motivation of small manufacturers owned by producers in maintaining their business. This qualitative study uses interviews as data collection technique and uses the credibility criteria to test the validity of the data. The study finds 3 themes of the informant's motivation to maintain its business , namely ( 1 ) intrinsic motivation , ( 2 ) extrinsic motivation , and ( 3 ) preservation of cultural motivation. Three themes that have been found can be implicated theoretically on the 5 levels of needs theory and the expectation theory of Abraham Maslow. The practical implication of this study is the fact that Indonesia has many cultures and cultural ritual devices, these facts create opportunities for other entrepreneursto develop a culture in Indonesia.